ETIKA PELAYANAN ADMINISTRASI DALAM MEWUJUDKAN GOOD GOVERNANCE DI KANTOR DESA KOLAM KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG : Indonesia - Ervan Ginting; Sondang Ruth Lovenia Sinaga (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2023)
AbstractEthics in carrying out organizational activities is very important in every life, both in community life and within the government environment. Ethics is often described as a reference for acting towards society. Ethics is also associated with the science of human behavior and decency which concerns norms or rules regarding good and bad behavior or traits. Ethics is a reference for bureaucrats to manage government towards good governance. Ethics in bureaucracy is very clearly regulated, but in real conditions today it is very much a concern. Bureaucratic behavior often goes beyond the rules which not only affects the environment but also influences the work culture which ultimately has an impact on society. In this case, the researcher's aim in the research is to find out the ethics of administrative services in realizing good governance at the Kolam Village Office, Percut Sei Tuan District, Deli Serdang Regency. The type of research in this research is descriptive research using qualitative research methods and using interview data collection techniques. Based on the results of interviews as well as observations and observations made by researchers in the field, it was found that the employees at the Pond Village Head's Office, Percut Sei Tuan District, Deli Serdang Regency, had carried out every task given to them well.